The Perception on Pathology Museum in Learning Pathology: A Survey of Undergraduate Medical Students at the Universiti Kuala Lumpur Royal College of Medicine Perak - Norain Karim; Muhammad Razif Jamil; Muhamad Aizuddin Mohd Latip; Adib Rifqi Azman; Muhammad Iqbal Hafi Nor Aizuddin; Amir Hakim Muhamad Nor; Muhammad Aiman Fahmi Abdul Mutalib; Roswati MN (Asian Journal of Medicine & Health Sciences, 2022)
Background: Pathology has traditionally been taught at medical schools through theoretical and practical teaching activities, oral lectures, clinical autopsies, and the display of macro-and microscopic specimens in pathology museums. On the other hand, the role of pathology museums has declined significantly in recent years. This study aimed to assess the perception of Bachelor of Medicine and Surgery (MBBS) students in using the pathology museum of the Universiti Kuala Lumpur, Royal College of Medicine Perak (UniKL RCMP) and its role in teaching pathology. Methods: A cross-sectional study was conducted as an online survey on 284 MBBS students using a self-administered, questionnaire. The questionnaire include sociodemographic characteristics of medical students, their basic knowledge, attitude and their perception towards pathology museum. Results: The response rate to the online survey was 100% (n=284) Most respondents (n=265, 93.31%) had good perceptions of the pathology museum. Eighteen respondents (6.34%) were neutral about the pathology museum, and one respondent had a poor perception. Despite the good perception, about half (53.5%) of students only sometimes visit the museum. Conclusion: The study revealed that undergraduate medical students of UniKL RCMP have a good perception of the pathology museum, and the highest frequency is seen in Year 5 (senior level) medical students. Students welcomed any improvement to the pathology museum, especially the incorporation of innovative technology.